Home monitoring - Mais Jamous; Hadeel Dwikat; Amani taqateq (My University, 2010)
The idea of "home monitoring" project, is a system makes you ablt to observe any place you want without the need of internet connection or wires.This project deals with a PC to do the monitoring through a camera. The camera is controlled by an application written in C# by the Visual studio 2005.NET and the Matlab,a keypad is connected to the system as a switch for the transmission.The software in our projects has two aims. One to control the camera in taking photos or videos and track people. The second part aims together with XBee module (wireless module) to transmit and do the monitoring from a specific distance. XBee module consists of two transceivers. one connected to the first computer serially and the other connected to another computer for who wants to monitor.The keypad code works as switch with code, so whenever you insert the right code you can stop or start the transmission through cutting the power from the wireless module other wise nothing happens